Bone neoformation of a novel porous resorbable Si‐Ca‐P‐based ceramic with osteoconductive properties: physical and mechanical characterization, histological and histomorphometric study. Issue 11 (18th January 2016) - De Aza, Piedad N.; Mate‐Sanchez de Val, Jose E.; Baudin, Carmen; Perez Albacete‐Martínez, Carlos; Armijo Salto, Antonio; Calvo‐Guirado, Jose L.
Abstract: Objective: The aims of the present work were to study a new porous Nurse's A ceramic (Si‐Ca‐P‐based material) bone substitute and examine its mechanical properties in vitro and the biocompatibility, osteoconductivity and resorption process in vivo . Materials and method: Porous ceramic scaffolds were prepared by solid‐state reaction and implanted in critical‐sized defect created in 15 NZ rabbits. Strength values were determined by the diametrical compression of disk test. Weibull analyses were performed following the European Standard for technical ceramics EN‐843‐5: 1996, considering 90% of confidence intervals. Results were correlated with scanning microscope observations of fracture surfaces. Implanted scaffolds were characterized by histological and histomorphometric point of view. Results: The parameters of the Weibull distribution of strength, determined by diametrical compression of disks, were modulus m = 13, and characteristic strength σ0 = 0.60 MPa (90% confidence limit: m = 7.2–17.6, σ0 = 0.570–0.578). Porous calcium silicophosphate scaffolds showed significantly more bone formation in the pores and in the periphery of the implant than the control group. Histomorphometric analysis revealed that the ceramic scaffold (62.23 ± 0.34*) produced higher values of bone‐to‐implant contact (BIC) percentages (higher quality, closer contact); moreover, defect closure was significative in relation with control group. Conclusions: The porous calcium silicophosphate ceramic is biocompatible, partially resorbable and osteoinductive material. This rabbit study provides radiological and histological evidences confirming the suitablity of this new material for bone tissue regeneration on critical defects.